Application of the Process Genre Approach for improving writing - Fadhliatul Ghina (Universitas Syiah Kuala, 2016)
This study intended to find out if there was a significant difference in writing ability between students who were taught writing using the Process Genre Approach (PGA) and those who were taught writing using the teacher’s usual approach. Two classes were taken using random sampling, one for the experimental group (EG) and the other for the control group (CG), with 24 students in each group from eleventh graders in Nurul Ulum MA Peureulak. Data, from the results of pre-tests and post-tests, was collected for quantitative analysis of the students’ writing abilities. The results from the analysis showed that the mean of the post-test scores from the EG was 67 whilst that from the CG was 53. The results from the t-test showed that the students who were taught using the PGA performed significantly better in writing than those who were taught the standard way. Analysis of the students’ writing ability showed more than 20 % improvement in four aspects of writing: organization, structure/grammar, content/idea and mechanics. The EG achieved significant improvement in all aspects of their writing ability than the CG so we can conclude that using the PGA can improve EFL writing ability more than present standard teaching-learning for EFL writing.